Analysis of the current situation and factors influencing the utilization of somatic and somatic-mental disorder comorbidity and health services among middle-aged and older adult people in China - Mo Xue; Qianqian Zhang; Jialing Wu; Kan Tian (Frontiers in Public Health)
BackgroundThe aging process has led to a significant increase in the prevalence of somatic chronic diseases (e.g., cardiovascular diseases, diabetes) among the middle-aged and older adult population. Additionally, this demographic is also susceptible to mental disorders (e.g., depression, anxiety). However, most studies in China focus on somatic chronic disease comorbidities, with less attention on comorbidities between somatic and mental disorders, as well as health service utilization.PurposeTo investigate the factors influencing the comorbidities of somatic and somatic-mental disorder and the status of health service utilization among middle-aged and older adult individuals in China.MethodsData from the 2020 China Health and Retirement Longitudinal Study (CHARLS) were analyzed, including 16,565 middle-aged and older adult individuals. Among them, 9,498 had somatic chronic disease comorbidities, and 4,577 had somatic-mental disorder comorbidities. Logistic regression was used to analyze factors influencing comorbidity and health service utilization. Spatial distribution maps were created using ArcGIS 10.8 software, and association rules were mined using IBM SPSS Modeler 18.0 and R 4.4.1.ResultsThe prevalence of somatic chronic disease comorbidity (57.34%) was higher than that of somatic-mental disorder comorbidity (27.63%). The patterns of comorbidity exhibited a complex network structure, with arthritis or rheumatism, hypertension, and stomach or other digestive disorders serving as core nodes. Dispositional factors (e.g., gender, age) and demand factors (e.g., number of comorbidities, self-rated health) had a significantly greater influence on the risk of comorbidities and health service utilization behaviors than enabling factors (e.g., household income, basic health insurance). Patients with somatic-mental disorder comorbidities had 1.09 times higher outpatient utilization compared to those with somatic chronic disease comorbidities (95% CI, 1.01 to 1.18). The average number of outpatient visits was also higher for the somatic-mental disorder comorbidities (2.55 ± 2.81 visits) than the somatic chronic disease comorbidities (2.34 ± 2.69 visits).ConclusionPay attention to the variations in the distribution of various combinations of comorbidity patterns within the population and develop targeted treatment strategies and preventive measures. Emphasize enhancing patients’ self-management skills and health literacy, also considering economic factors. Elevate the significance of mental health services and management, strengthen patients’ social support networks, and reduce social stigma and discrimination.